Advances in preventive vaccine development against HTLV-1 infection: A systematic review of the last 35 years - Carolina Souza Santana; Felipe de Oliveira Andrade; Greice Carolina Santos da Silva; Jéssica Oliveira de Souza Nascimento; Raissa Frazão Campos; Marta Giovanetti; Marta Giovanetti; Luciane Amorim Santos; Luciane Amorim Santos; Luana Leandro Gois; Luana Leandro Gois; Luiz Carlos Júnior Alcantara; et al. (Frontiers in Immunology, 2023)
IntroductionThe Human T-lymphotropic virus type 1 (HTLV-1) was the first described human retrovirus. It is currently estimated that around 5 to 10 million people worldwide are infected with this virus. Despite its high prevalence, there is still no preventive vaccine against the HTLV-1 infection. It is known that vaccine development and large-scale immunization play an important role in global public health. To understand the advances in this field we performed a systematic review regarding the current progress in the development of a preventive vaccine against the HTLV-1 infection.MethodsThis review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA®) guidelines and was registered at the International Prospective Register of Systematic Reviews (PROSPERO). The search for articles was performed in PubMed, Lilacs, Embase and SciELO databases. From the 2,485 articles identified, 25 were selected according to the inclusion and exclusion criteria.ResultsThe analysis of these articles indicated that potential vaccine designs in development are available, although there is still a paucity of studies in the human clinical trial phase.DiscussionAlthough HTLV-1 was discovered almost 40 years ago, it remains a great challenge and a worldwide neglected threat. The scarcity of funding contributes decisively to the inconclusiveness of the vaccine development. The data summarized here intends to highlight the necessity to improve the current knowledge of this neglected retrovirus, encouraging for more studies on vaccine development aiming the to eliminate this human threat.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier (CRD42021270412).